Masculinity, sexism and populist radical right support - Coffe, Hilde; Fraile, Marta; Alexander, Amy; Fortin-Rittberger, Jessica; Banducci, Susan (Frontiers in Political Science, 2023)
The gender gap in populist radical right voting - with women being less likely to support populist radical right parties than men - is well-established. Much less is known about the interplay between gender, masculinity and populist radical right voting. This study investigates the extent to which masculinity affects women and men’s likelihood of supporting populist radical right parties. Focusing on sexism as a link between masculinity and populist radical right support, we put forward two mechanisms that operate at once: a mediating effect of sexism (sexism explains the association between masculinity and populist radical right voting) and a moderating effect of sexism (the impact of masculinity is stronger among citizens scoring high on sexism compared with citizens with low levels of sexist attitudes). Relying on original Spanish data collected at the end of 2020 and studying support for the Spanish populist radical right party VOX, we find support for both mechanisms, at least among men. First, sexism explains about half of the link between masculinity and populist radical right support among men; showing a mediation effect. Second, masculinity has a significantly stronger impact on the likelihood of supporting VOX among men scoring high on sexism; confirming a moderation effect.